Irradiation on teak and pine agroforestry system and the effect on growth of soybean - DJOKO PURNOMO; SYUKUR MAKMUR SITOMPUL (Society for Indonesian Biodiversity, 2006)
Teak and pines are the largest tree forests in Central of Java so that they are very potential to be developed as an argoforestry system. The average Relative Irradiation Fraction (RIF)â€™s in the teak and pines trees are 50% and 14% respectively. Meanwhile, soybean is sunloving crop potentially to be cultivated in the agroforestry system. The aim of the research was to study the response of the soybean (Glyicine soya) varieties to the tree canopy pruning. The experiment was conducted at teak and pines forest area (vertisol and ultisol soil type respectively) arranged in split plot design. The main plot factor was pruning (no pruning and pruning) and the sub plot factor was variety (Wilis, Pangrango and Brawijaya). The teak and pines canopy pruning (50% lower part of canopy) increases the incident irradiation among the trees by 70%-89% or equal to 600-1000 Î¼ mol m-2 s-1 and 80% or 840 Î¼ mol m-2 s-1 respectively. The increase in the irradiation among the trees enhances the photosynthetic rate of soybean. The response of the soybean to the enhancing irradiation is higher in specific leaf area (SLA). Biomass production and seed yield of the soybean increases due to the canopy pruning. The seed yield of soybean increase respectively from 0.12 to 0.57 tons ha-1 and from 0.78 to 1.74 tons ha-1 in no pruning and pruning teak and pines agroforest. The Pangrango variety produces the highest yields of seed, thus it is potential to be cultivated as intercrops in a teak and pines agroforestry system.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: soybean, teak, pines, agroforestry.